Numerical simulation of ternary nanofluid flow with multiple slip and thermal jump conditions - Alshahrani, Saad; Ahammad, N. Ameer; Bilal, Muhammad; Ghoneim, Mohamed E.; Ali, Aatif; Yassen, Mansour F.; Tag-Eldin, Elsayed (Frontiers in Energy Research, 2022)
This study addresses the consequences of thermal radiation with slip boundary conditions and a uniform magnetic field on a steady 2D flow of trihybrid nanofluid over a spinning disc. The trihybrid nanocomposites are synthesized by the dispersion of aluminum oxide (Al2O3), zirconium dioxide (ZrO2) and carbon nanotubes (CNT) in the water. The phenomena are characterized as a nonlinear system of PDEs. Using resemblance replacement, the modeled equations are simplified to a nondimensional set of ODEs. The Parametric Continuation Method has been used to simulate the resulting sets of nonlinear differential equations. Figures and tables depict the effects of physical constraints on energy and velocity profiles. According to this study, the slip coefficient enormously decreases the velocity field. For larger approximations of thermal radiation characteristics and heat source term boosts the thermal profile. This proposed model will assist in the field of meteorology, atmospheric studies, biological technology, power generation, automotive manufacturing, renewable power conversions, and detecting microchips. In regard to such kinds of practical applications, the proposed study is being conducted. The study is unique due to slip conditions and ternary fluid, and it could be used by other scholars to acquire further about nanofluid thermal exchangers' performance and stability.